Prophylactic uterotonic agent to avoid postpartum bleeding on normal vaginal delivery - Ibnu Pranoto, Ibnu Pranoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Objective: To compare the volume of blood loss after normal vaginal delivery that have been givenÂ prophylactic uterotonic agents, 2.5 IU oxytocin, 5 IU oxytocin, 2.5 IU oxytocin plus 0.2 mg ergometrin,Â and 5 IU oxytocin plus 0.2 mg ergometrin.Methods: A Randomized control trial study was performed, 22 normal vaginal deliveries were given 2.5 IU oxytocin. 5 IU oxytocin was for 26 normal deliveries, 2.5 IU oxytocin plus 0.2 mg ergometrin for 29 deliveries and 5 lU oxytocin plus 0.2 mg ergometrin for 27 deliveries. The agents were administered intramuscularly or intravenously at a time of crowning. One way-anova test was used in this study. Intrapartum mothers with the normal vaginal delivery in Obstetrics and Gyneclogy Department of Sardjito General Hospital, Yogyakarta and Soeradji General Hospital, Klaten, between April 1t and July 28th 1988. Results: There is no significant difference between the second stage blood loss in the deliveries given 2.5 IU and 5 IU oxytocin with or without ergometrin. On the other hand, administration of 2.5 IU oxytocin has been statistically significant to reduce the mean blood loss on the third stage of labor compared to the other regiments. Prophylactic 2.5 IU and 5 IU oxytocin with or without ergometrin did not show any significant difference on the fourth stage of labor. The mean of blood loss after normal vaginal delivery was statisticaly significantly reduced by giving 2.5 IU oxytocin as the prophylactic agent compared to the other treatments in this study.Conclusion: The administering of 2.5 IU oxytocin was more significant in preventing postpartum bleeding in the third stage of labor and the postpartum bleeding. Ergometrin addition to oxytocin was not proved to decrease the blood loss in any stage of labor and portpartum bleeding as well.Keywords : Prophylactic uterotonic agents - oxytocin - ergometrin - normal vaginal delivery - postpartum bleeding.